Taksiran Akumulasi Biomassa atas Permukaan pada Eksperimen Restorasi Lahan Gambut Bekas Terbakar, Area Transisi Cagar Biosfer Giam Siak Kecil-Bukit Batu, Riau, Sumatera Indonesia - GUNAWAN, HARIS; MUDIYARSO, DANIEL; MIZUNO, KOSUKE; KOZAN, OSAMU; SOFIYANTI, NERY; INDRIYANI, DIAN; SEPTIANI, DIEN; LESTARI, ISKA (Jurusan Biologi FMIPA Universitas Riau, 2016)
The Giam Siak Kecil-Bukit Batu Biosphere Reserve was managed by zonation as a approach for multibenefitof management goals. This Bioshere Reserve has a fairly high carbon stock stored in its naturalpeat swamp forest ecosystems. Nevertheless, the condition of the peat swamp forest in the BiosphereGiam Siak Kecil-Bukit Batu currently has been destructed, especially in the buffer and transition zones.The threats of protected areas are not only coming from forest fire factors, but also from encroachmentand illegal logging. Therefore, it requires a recovery effort. This research aims to determine the survivalrate and to estimate the above ground biomass accumulation of the main tree species of peat swamp forestthat used to restore the burnt peat. The estimated total biomass accumulation on the surface was measuredÂ using allometric equations. Result of this research proved that Jelutung tree (Dyera polyphylla) has thebest survival rate among the trees (98%), while banana tree (Mezzettia parviflora) has lower survival rate( 35%). The highest total biomass accumulation was found in Jelutung (Dyera polyphylla) (499.015kg/ha/year, while the lowest total biomass accumulation was found in Meranti batu (Shorea uliginosa)(88.867 kg/ha/year). A total of nine pioneer species were identified i.e. Tenggek burung (Euodia sp),kayu ara (Ficus sp), mahang (Macaranga triloba), karet (Havea brasiliensis), sendayan (Scleriasumatrensis), alang-alang (Imperata cylindrica), senduduk (Melastoma malabathricum), paku-pakuan(Neprolepis hirsutula) and rumput teki (Cyperus rotundus). The total biomass accumulation of earlysuccession in all types of vegetation pioneer is 338,91 kg/ha.Key words: Above Ground Biomass Accumulation, restoration, vegetasion succession, burned peatland,Survival Rate.